Adapting grazing practices to limit the reforestation of mountainous summer pastures: A process-based approach. (October 2016) - Vacquié, Laure A.; Houet, Thomas; Sheeren, David; de Munnik, Nicolas; Roussel, Virginie; Waddle, Julien
Abstract: European mountain landscapes are experiencing massive land-use changes and high rates of natural reforestation since the 1950s. Summer pastures are particularly sensitive to those dynamics since their natural state depends on human activities. A process-based model - SHIELD (Simulating Herd Impact on Encroachment in upLanD) – has been developed to identify the key leverages of pastoral practices to limit the natural reforestation in the Haut-Vicdessos (Pyrenees Mountains, France). Simulations are compared to observed land cover changes to validate the model's structure. Scenarios are simulated to assess various grazing practices on reforestation dynamics: a baseline scenario and three scenarios with contrasted pastoral management: (i) reintroducing herds with no human supervision, (ii) reintroducing herds supervised by a shepherd and (iii) increasing the cattle load without supervision. Results show that supervising the intensity of land units' occupancy can be as efficient as increasing the cattle load to limit the ongoing trends of reforestation. Highlights: A process-based model was developed to simulate interactions between grazing activities and land cover dynamics. Vegetation successions, cattle activity and tree growth processes are represented through the SHIELD model. The model integrates knowledge from local experts, agricultural practices and remote sensing data. Scenarios are developed to assess various grazing practices on reforestation dynamics. Grazing routines may be more efficient to limit reforestation than grazing intensity. Results highlight the influence of grazing intensity and grazing routines to limit natural reforestation.